电力系统有功和无功功率充裕度评估 = Adequacy evaluation of active and reactive power in power systems - 秦文萍 Qin, Wenping (2014)
无功功率与系统电压稳定及电压崩溃现象密切相关,其对系统稳定运行具有重要意义。然而,在传统可靠性评估中,很少计及无功功率的影响。文中分别从有功和无功功率两个角度对电力系统可靠性进行研究。在评估中,考虑了有功和无功功率短缺以及由于系统故障引起的电压扰动问题,在事故后采用三级切负荷技术来确定有功和无功功率对电力系统可靠性的影响,并找出最经济的方法来缓解网络参数越限问题。Reactive power plays an important role in power system reliability as it is closely related to system voltage stability and voltage collapse. However，the reactive power related reliability issues are seldom emphasized in conventional power reliability evaluation.This paper studies the power system reliability from the perspective of active and reactive power，respectively.Active and reactive power inadequacy and the associated voltage perturbation due to system failure are considered in reliability evaluation of power systems.A three-stage load shedding technique for past contingencies are implemented to determine the influence of active and reactive power on system reliability and to find an optimal way to relieve network violation.